Improving Students’ Reading Comprehension Through The Scanning Technique At SMA Negeri 1 Tondano - Batubuaja, Karenina; Liando, Nihta V. F; Wongkar, Yapi (Program Studi Pendidikan Bahasa Inggris, 2025)
Reading is the process of getting information by understanding the meaning of the text being read, reading is called receptive skills and these skills basically are the ways in which people extract meaning. Reading comprehension is defined as the ability to analyze text, comprehend its meaning, and integrate it with prior knowledge.‘ Teaching Reading Comprehension in order to help their pupils become better readers and to increase their reading comprehension in accordance with their English reading ability'. Improve is make something better in this case especially to make someone better in reading through scanning technique. It is commonly acknowledged that one of the techniques in reading is scanning technique. The technique is needed not only to overcome students’ difficulties, but also to improve students’ reading comprehension. Scanning is the technique for quickly finding specific information in a text while ignoring its broader meaning, it searches for keywords or idea in a written text. In addition use scanning technique is effective in improve students’ reading comprehension.